Pendidikan sebagai Sarana Penyalur Pengetahuan dalam Filsafat Islam - Desi Gustiara; Rizky Azzahra; Herlini Puspika Sari (Reflection : Islamic Education Journal, 2024)
Education has a very important role in Islamic philosophy as the main means of broadcasting, maintaining and internalizing knowledge that includes intellectual and spiritual aspects. Islamic educational philosophy views education not only as a process of transferring knowledge, but also as a medium or tool in the formation of morals and increasing individual spirituality. This article aims to research and observe the concept of education in Islamic philosophy through literature studies and analysis of classical texts by Muslim thinkers, such as Al-Ghazali and Al-Farabi, which highlight the importance of balance between intellectual intelligence and spiritual wisdom. Education in the Islamic view plays a very important role in developing individual morals and forming an ethical society, as well as in the application of Islamic values ​​worldwide. The results of the study show that education according to Islamic philosophy does not only focus on worldly aspects, but also on the formation of a complete human being, both intellectually and spiritually. With integrated education, it is hoped that individuals will be born who have superior personalities who are able to contribute positively to society. Thus, education in Islamic philosophy functions as a very important means or instrument for conveying and preserving the noble values ​​that have been passed down by Muslim intellectuals from generation to generation, as well as being a path towards the formation of a harmonious, ethical and civilized society.